STUDENTS’ PERCEPTION ON THE USE OF VIDEO PROJECT IN SPEAKING CLASS AT SECOND GRADE SMPN 4 BANGKALA BARAT - Syarah, St. Nurdaeni; Abdullah, Nurdevi Bte; Asmayanti, St (FKIP Unismuh Makassar, 2025)
The objectives of the research to find out the student’s perception on the implementation and the content of video project in speaking class. The researcher used descriptive method to find the students’ perception on video project in speaking skill. The subject of the research 10 students from SMPN 4 Bangkala Barat. The instrument of the research used interview. The result of the research showed that students have a positive perception about the video project practicing their speaking skills and the video can be used as one of the teaching media in students' speaking classes. Video project is a good solution to improve speaking, increase vocabulary, and improve students' pronunciation in English. The teachers contribution in the class also supports students positive perception toward the video project in speaking class.